Expectations of Non-Malaysian Restaurant Managers towards Halal Certification / Sharifah Zannierah Syed Marzuki ... [et al.] - Syed Marzuki, Sharifah Zannierah; Buyong, Siti Zahrah; Yahya, Wan Kalthom; Mohammad Kamaruddin, Laila; Kamall Khan, Yasmin; Erjon, Duka (2637-0301 (e-ISSN), 2018)
Halal food industry has gained tremendous demand from all over the world that includes both the Muslim and non - Muslim consumers thus contributing to significant economic growth in the halal market. Previous halal studies has been focusing on halal food purchasing, halal marketing, halal tourism and halal meat. However, research on halal hospitality industry that look into the restaurant sector is very sparse. Therefore, this paper aims to investigate on the expectations on non- Malaysian restaurant managers toward halal certification as Malaysians do prefer to eat non local food. Taking into considerations the number of restaurants that offer non-local food is high in Nilai and Cyberjaya, a qualitative survey was performed on three restaurant owners/managers. The findings show that the managers have very positive understandings on halal connotations and the implications on their restaurants as far as the plural society in Malaysia is concerned. Halal attributes that include trust, hygienic and traceability were related to signify halal certification. Future research may consider looking into restaurant managers and halal certification worldwide as return visit is crucial in attracting the Muslim customers in particular.